The World of Anaconda: the myth of the snake-canoe and its relationship with the stilt villages from eastern amazon - Navarro, Alexandre (Brasiliana: Journal for Brazilian Studies, 2021)
Amazonian ethnography relies on a world created by an anaconda, an ancestral creator. The story that myths tell is that the Amazon River is the metaphor of an anaconda; a large, meandering reptile. While the Anaconda sails along the great river, it populates the riverbanks, creating the Indian villages along its margins. This is why the anaconda is a snake-canoe. Amazonian societies are classified by archeology as belonging to the Polychrome Tradition of the Amazon (TPA). This research suggests that stilt villagers in eastern Amazonia, where shamanism played a role in communicating with animals, also shared this myth. The anaconda embodied in ceramic archaeological sites is as a memory of this complex indigenous narrative as it develops across time.